First records of the genus Cambalida Simon, 1909 (Araneae: Corinnidae, Castianeirinae) from Asia, with the description of two new species from India and one new combination - Murthappa, Prashanthakumara S.; Prajapati, Dhruv A.; Sankaran, Pradeep M.; Sebastian, Pothalil A. (Zootaxa, 2016)
The hitherto Afrotropical corinnid spider genus Cambalida Simon, 1909 is recorded from Asia for the first time. Detailed morphological descriptions and genitalic illustrations of two new species, C. deorsa sp. n. and C. tuma sp. n. from India, are provided. One new combination is proposed: Cambalida flavipes (Gravely, 1931) comb. nov. The occurrence of distal femoral constrictions of III and IV legs of both male and female are recognised as additional somatic features for the genus Cambalida. The current distribution of all the three Indian Cambalida spp. is mapped.